Streptococcal peptides and their roles in host-microbe interactions - Wahlenmayer, Emily R.; Hammers, Daniel E. (Frontiers in Cellular and Infection Microbiology, 2023)
The genus Streptococcus encompasses many bacterial species that are associated with hosts, ranging from asymptomatic colonizers and commensals to pathogens with a significant global health burden. Streptococci produce numerous factors that enable them to occupy their host-associated niches, many of which alter their host environment to the benefit of the bacteria. The ability to manipulate host immune systems to either evade detection and clearance or induce a hyperinflammatory state influences whether bacteria are able to survive and persist in a given environment, while also influencing the propensity of the bacteria to cause disease. Several bacterial factors that contribute to this inter-species interaction have been identified. Recently, small peptides have become increasingly appreciated as factors that contribute to Streptococcal relationships with their hosts. Peptides are utilized by streptococci to modulate their host environment in several ways, including by directly interacting with host factors to disrupt immune system function and signaling to other bacteria to control the expression of genes that contribute to immune modulation. In this review, we discuss the many contributions of Streptococcal peptides in terms of their ability to contribute to pathogenesis and disruption of host immunity. This discussion will highlight the importance of continuing to elucidate the functions of these Streptococcal peptides and pursuing the identification of new peptides that contribute to modulation of host environments. Developing a greater understanding of how bacteria interact with their hosts has the potential to enable the development of techniques to inhibit these peptides as therapeutic approaches against Streptococcal infections.